PROJECT-BASED LEARNING AND STUDENT CREATIVITY IN ART, CULTURE, AND CRAFTS EDUCATION IN ELEMENTARY SCHOOLS: A CLASSROOM ACTION RESEARCH STUDY - Wilda Awwaliyatun Ni'mah; Mahmud; Jetra Viktoria (Referensi Islamika: Jurnal Studi Islam, 2026)
This study was conducted to describe the implementation of the Project-Based Learning (PjBL) model and to determine the increase in creativity among fourth-grade students at SDN 189/VI Pinang Merah, Merangin Regency, involving 23 students in the Arts, Culture, and Crafts (SBdP) subject. This study was motivated by the low level of student creativity, as evidenced by their limited ability to develop ideas, produce original works, and their low level of engagement in the learning process. This study employed the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, conducted over two cycles. The research subjects consisted of 23 fourth-grade students. Data collection techniques included observation, interviews, documentation, and a student creativity questionnaire. Creativity was measured based on four indicators: fluency, flexibility, originality, and idea development. The study’s success was defined as students’ creativity levels reaching ≥80%. Data were analyzed using quantitative and qualitative descriptive methods in each learning cycle. The results of the study indicate that the implementation of the Project-Based Learning (PjBL) model was followed by a gradual increase in student creativity. In the pre-cycle stage, student creativity reached 54.25%, falling into the “less creative” category. After implementing PjBL in Cycle I, student creativity increased to 65.26%, falling into the “moderately creative” category. In Cycle II, student creativity reached 85.76% and met the study’s success indicators. This improvement was evident in the aspects of idea fluency, flexibility of thinking, originality, and the ability to develop creative works. The results indicate that the implementation of PjBL has the potential to support the development of student creativity in SBdP learning within the context of this study. However, this study was limited to a single class of 23 students, conducted over two action cycles, and did not include a control group; therefore, the findings cannot yet be widely generalized. The novelty of this study lies in its description of the implementation of Project-Based Learning in Arts, Culture, and Crafts (SBdP) instruction through Classroom Action Research at an elementary school located in a rural area with limited learning resources. These findings provide a contextual overview of the application of PjBL in supporting the development of student creativity and can serve as a reference for teachers in designing lessons that are more creative, innovative, and suited to the characteristics of rural elementary schools.